TEACHER IDENTITY AGENCY IN LANGUAGE TEACHING: IMPLICATIONS FOR LANGUAGE TEACHER EDUCATION - Weng, Zhenjie (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
While there have been separate investigations into language teacher identity and agency, a conspicuous gap existed in the literature as no systematic synthesis had been conducted to unravel the interconnected relationship between these two crucial concepts within the field of language teaching. This study endeavours to bridge that gap, providing a more holistic understanding of what identity and agency truly mean in the context of language teaching and teacher education. Through a meticulous analysis of 29 selected articles, it delves into five pivotal aspects: the diverse forms of identities, the multifaceted manifestations of agency, the circumstances under which language teachers exercise their identity agency, the intricate relationships between identity and agency, and the profound impact of this interplay on language teaching. Notably, one salient finding reveals that identity position emerges as the most extensively examined form of identity, with teachers constantly navigating the dynamic space between their desired and actual identities in response to varying teaching contexts. This finding not only sheds light on the inner workings of language teacher identity construction but also holds implications for how language teacher educators can better support pre-service and in-service teachers in their professional growth.